Polymorphisms in MC1R and ASIP genes and their association with coat color phenotypes in llamas (Lama glama) - Daverio, Maria Silvana; Rigalt, Francisco Antonio; Romero, Sandra Raquel; Vidal Rioja, Lidia Beatriz; Di Rocco, Florencia (2018)
The melanocortin 1-receptor (MC1R) and the agouti signaling protein (ASIP) are the major genes controlling the type and location of pigments produced in mammals. In recent years, polymorphisms in these genes have been associated with coat color variation in a number of species. Llamas (Lama glama) are characterized by a great diversity of coat colors. However, the genetic basis of coat color determination is still unknown. Here, we sequenced the MC1R and ASIP genes in llamas and studied the association between the polymorphisms identified and the coat color. Sequence analysis revealed ten nonsynonymous single nucleotide polymorphisms in the MC1R gene. Three main haplotypes were identified, none of which were completely associated to a particular color phenotype. However, significant association was detected between the MC1R*1 haplotype and the presence of pigmented coat (P < 0.0001). Compared to the wild allele, MC1R*1 carried two amino acid substitutions, p.G126S and p.V87 M. This last replacement occurs at a highly conserved residue among mammals and the same substitution has been previously associated to melanic phenotypes in avian species. Furthermore, two polymorphisms in ASIP exon 4, a 57 bp deletion (c.325_381del) and c.292C > T that are both predicted to have a deleterious effect on the protein, were found in homozygous state or combined in most llamas with eumelanic coat.